EmaxDB: Availability of a first draft genome sequence for the apicomplexan Eimeria maxima. - Blake, D; Alias, H; Billington, K; Clark, E; Mat-Isa, M; Mohamad, A; Mohd-Amin, MR; Tay, Y; Smith, A; Tomley, F; Wan, K (2012)
Apicomplexan parasites are serious pathogens of animals and man that cause diseases including coccidiosis, malaria and toxoplasmosis. The importance of these parasites has prompted the establishment of genomic resources in support of developing effective control strategies. For the Eimeria species resources have developed most rapidly for the reference Eimeria tenella Houghton strain (http://www.genedb.org/Homepage/Etenella). The value of these resources can be enhanced by comparison with related parasites. The well characterised immunogenicity and genetic diversity associated with Eimeria maxima promote its use in genetics-led studies on coccidiosis and recommended its selection for sequencing. Using a combination of sequencing technologies a first draft assembly and annotation has been produced for an E. maxima Houghton strain-derived clone (EmaxDB; http://www.genomemalaysia.gov.my/emaxdb/). The assembly of a draft genome sequence for E. maxima provides a resource for comparative studies with Eimeria and related parasites as demonstrated here through the identification of genes predicted to encode microneme proteins in E. maxima.